2002
DOI: 10.5038/1827-806x.31.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Karst subsidence in South-Central Apulia, Southern Italy

Abstract: Subsidence in the karst of Apulia (Southern Italy), one of the classical karst areas of Italy, is described in this paper. The carbonate rocks that make up the geological structure of the Apulia region are affected by subsidence, which is of different type and intensity depending upon geological , topographical, and hydrogeological conditions. In particular, we discriminate between inland subsidence and coastal subsidence. Inland subsidence is generally restricted to the presence of individual cavities, either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Several other studies regarding sinkhole distribution have shown the clustering of sinkholes along fault lineaments (Delle Rose and Parise, 2002;Abelson et al, 2003;Doctor et al, 2008;Del Prete et al, 2010) and the decreasing number of sinkhole occurrences with increasing distance from the fault (Hyland et al, 2006;Billi et al, 2007). A lineament of sinkholes can also be used to find hidden faults (Closson and Abou Karaki, 2009).…”
Section: Releasing Bendmentioning
confidence: 98%
“…Several other studies regarding sinkhole distribution have shown the clustering of sinkholes along fault lineaments (Delle Rose and Parise, 2002;Abelson et al, 2003;Doctor et al, 2008;Del Prete et al, 2010) and the decreasing number of sinkhole occurrences with increasing distance from the fault (Hyland et al, 2006;Billi et al, 2007). A lineament of sinkholes can also be used to find hidden faults (Closson and Abou Karaki, 2009).…”
Section: Releasing Bendmentioning
confidence: 98%
“…They occur on outcropping carbonatic bedrock or on bedrock with thin sedimentary cover (Macaluso et al 2002;Delle Rose and Parise 2002;Delle Rose et al 2004a, b). However, a few sinkholes are related to anthropogenic features (i.e., roof collapse of artificial cavities due to human activity).…”
Section: Sinkhole Classification According To Italian Case Historiesmentioning
confidence: 98%
“…Further, Triassic evaporites in the northern reaches of Apulia are also affected by sinkholes (Fidelibus et al, 2011). In many sectors of Salento, sinkholes are so widespread that they have become the main landform, especially along the low shorelines of both the Adriatic and Ionian seas (Delle Rose and Parise, 2002;Bruno et al, 2008). Sinkholes have often been modified by man to gain land for agricultural practices or to be used as swallet sites to mitigate flood hazards during heavy rainfall.…”
Section: Introductionmentioning
confidence: 99%